Assessing Conflicts in Forest Management Among Different User Groups: A Case Study of Mwekera Forest Reserve - Phiri, Ackim (Journal of Sustainability and Environmental Management, 2024)
Conflict resolution is a vital component of effective forest resource management, attracting the attention of various stakeholders in many protected forest areas in Zambia. Challenges in achieving peaceful resolutions, disputes over land control, over-exploitation of forests for charcoal production, and agricultural expansion have led to the shrinkage of forest areas. Effective conflict resolution strategies, institutional arrangements, and a thorough understanding of conflict sources are essential for maintaining healthy forests, fostering a peaceful society, and combating the impacts of climate change. While several researchers have studied conflict management in some protected areas across the country, few studies have focused specifically on conflict resolution and management in Mwekera Forest Reserve. This study aimed to understand conflicts in forest management among different user groups. A random sampling technique was employed, with one of the five communities in the area—Mabote—randomly selected for the study. Data was collected using a structured survey questionnaire, which included questions on the socio-demographic status of respondents, causes of conflicts, institutional arrangements in conflict management, and control measures in practice. Additionally, in-depth interviews with key informants were conducted to gather data not captured by the questionnaires. A total of 70 respondents from Mabote community participated in this study. The findings indicated that nearly half (46%) of respondents identified equitable benefit-sharing as crucial for conflict management in the forest reserve. This was followed by equal access to forest areas and products (28.4%), stakeholder engagement and participation (14.3%), and enhanced forest monitoring (9.2%). A smaller portion of respondents (2.1%) pointed to the need for improving laws and policies. The results suggest that current conflict management practices in the forest reserve are insufficient (46%) to ensure effective forest management, despite the increasing sources of conflict and forest degradation. The Forest Department emerged as the primary stakeholder in Mwekera Forest Reserve’s management, exercising total control, which has led to the exclusion of local communities from accessing the forest and its resources. Therefore, effective conflict resolution measures are essential to enable equitable resource access, sustainable forest management, and conflict mitigation in the reserve.